The Mediating Role of Self-Efficacy and Social Intelligence to Build Leadership Character through MBKM Program - Ika Yoga; Retnoning Ambarwati (UIN Raden Mas Said Surakarta, 2023)
The Merdeka Belajar Kampus Merdeka (MBKM) program aims to prepare students to face social, cultural, world of work, and rapid technological advances. One important aspect of this competency is leadership character, which can be formed through the MBKM program. This study aims to analyze the effect of the MBKM program on the formation of student leadership character with the mediation of self-efficacy and social intelligence. The research was conducted using a survey method of 50 students. The data were analyzed using PLS. The results showed that the MBKM program had a positive effect on the formation of student leadership character with the mediation of self-efficacy and social intelligence. In addition, it was found that self-efficacy and social intelligence mediate the relationship between the MBKM program and the formation of student leadership character. This study provides important implications for universities to pay more attention to the development of student leadership character through the MBKM program. In addition, this study also provides a theoretical contribution to the development of a model of student leadership character building through the mediation of self-efficacy and social intelligence.